Validity of pre and post-term birth rates based on the date of last menstrual period compared to early obstetric ultrasonography - Maria Nilza Lima Medeiros; Nádia Carenina Nunes Cavalcante; Fabrício José Alencar Mesquita; Rosângela Lucena Fernandes Batista; Vanda Maria Ferreira Simões; Ricardo de Carvalho Cavalli; Viviane Cunha Cardoso; Heloisa Bettiol; Marco Antonio Barbieri; Antônio Augusto Moura da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The aim of this study was to assess the validity of the last menstrual period (LMP) estimate in determining pre and post-term birth rates, in a prenatal cohort from two Brazilian cities, São Luís and Ribeirão Preto. Pregnant women with a single fetus and less than 20 weeks' gestation by obstetric ultrasonography who received prenatal care in 2010 and 2011 were included. The LMP was obtained on two occasions (at 22-25 weeks gestation and after birth). The sensitivity of LMP obtained prenatally to estimate the preterm birth rate was 65.6% in São Luís and 78.7% in Ribeirão Preto and the positive predictive value was 57.3% in São Luís and 73.3% in Ribeirão Preto. LMP errors in identifying preterm birth were lower in the more developed city, Ribeirão Preto. The sensitivity and positive predictive value of LMP for the estimate of the post-term birth rate was very low and tended to overestimate it. LMP can be used with some errors to identify the preterm birth rate when obstetric ultrasonography is not available, but is not suitable for predicting post-term birth.